Digital Syariah Banking System (DSBS) : Cash Waqf Determinants Promoting Innovation of Islamic Economic Development in Indonesia - Haidar, Abdullah; Herindar, Evania; Hendrasto, Nur; Chairiyati, Fauziah (UIN Sunan Kudus, 2024)
Cash waqf provides a new option for enhancing the growth of waqf transactions in Indonesia, particularly in Indonesia. Through the collaboration of BWI and Islamic banks utilizing financial technology (FinTech), an innovative DSBS, a digital banking system for sharia, to help with cash waqf transactions. It is anticipated that the presence of a system that facilitates cash waqf transactions will increase the desire of individuals to partake in cash waqf. This research aims to investigate which factors can motivate z generation and millennial in Indonesia to donate cash waqf through DSBS. This investigation included 200 participants. Using PLS SEM, this study indicates in which the research model is strategic because it satisfies all of the requirements. Additionally, research has shown that comfort, utility, and subjective norms all have an impact on z generation and millennial intentions or decisions about the usage of DSBS in Indonesia. The convenience and benefits of using DSBS to conduct cash waqf transactions are the most important factors in promoting the growth of cash waqf in indonesia. In order to create a more comprehensive research model, this study integrates the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB).